EFFICACY OF CLOTHIANIDIN 50 WDG AGAINST TERMITES IN SUGARCANE - Vinothkumar, B; Shanmugapriya, R; Sangamithra, S; Kuttalam, S (Journal of Sugarcane Research, 2019)
Two field experiments were conducted to study the efficacy of clothionidin 50WDG against termites Odontotermes obesus Rambur (Isoptera: Termitidae) of sugarcane at the Department of Agricultural Entomology, Tamil Nadu Agricultural University, Coimbatore during 2015 -2017. The experiments were conducted in a randomized block design with seven treatments replicated thrice with a plot size of 8 x 5 m. Applications of insecticides were made at the time of planting. Germination of sugarcane setts recorded at 30 days after planting (DAP) and termite infestation was observed at 60, 120 DAP and at harvest and the per cent infestation was calculated. Results revealed that, the per cent germination data indicated that the clothianidin 50 WDG @ 150 g a.i. ha-1 treatment recorded higher germination and it was on par with clothianidin 50 WDG @ 125 g a.i. ha-1. The above two treatments showed significantly higher germination per cent than all other treatments including standard checks and untreated control recorded the least germination per cent. The termite damage was minimum in the plots treated with the test chemical clothianidin 50 WDG @ 150 g a.i. ha-1 at all the days of observation and it was on par with the clothianidin 50 WDG @ 125 g a.i. ha-1. The above two treatments resulted significantly superior in controlling termite damage over other treatments. Clothianidin 50 WDG @ 125 g a.i. ha-1 and 250 g a.i. ha-1 does not have any phytotoxicity effect on sugarcane. The study on the impact of clothianidin 50 WDG on natural enemies in the sugarcane agroecosystem revealed that, insecticidal treatments in the planting did not adversely affect the population of natural enemies in the crop. Clothianidin 50 WDG at 150 g a.i. ha-1 registered significantly more cane yield followed by clothianidin 50 WDG at 125 g a.i. ha-1. Effect of clothianidin 50 WDG on yield parameters were recorded at the time of harvest and results indicated that commercial cane sugar (CCS) yield followed similar trend like cane yield whereas, Brix unit and POL per cent (Sucrose per cent) did not show any significant difference among the treatments. Hence it is concluded that, clothianidin 50 WDG @ 150 g a.i. ha-1 remained on par with clothianidin 50 WDG @ 125 g a.i. ha-1 have effectively controlled the termite infestation in sugarcane ecosystem.